Occupational risk assessment at Olive Oil mills: Limitations and new perspectives - Rodrigues, Matilde (2016)
Risk assessment is an essential tool to support risk decisions. However, this process may not always be applied effectively, and this can limit the quality of the preventative action. This is particularly critical in sectors that have a lot of micro and small companies, such as Olive Oil Mills (OOMs). To better understand how to improve the quality of the risk assessment at OOMs, this study aims to analyze the views of Occupational Safety and Health (OSH) practitioners on the key difficulties/limitations in this process and identify some improvements to current practices. This analysis was based on a questionnaire that was developed and given to 13 OSH practitioners working for OOMs. The results showed that the time available to perform the risk assessment is the major limitation. The need for a specific tool for risk assessment in the OOM sector was identified, and the use of accident reports from the entire sector was indicated as an alternative to the absence of data at company level.